2007
DOI: 10.1371/journal.pbio.0050228
|View full text |Cite
|
Sign up to set email alerts
|

The Scent of the Waggle Dance

Abstract: The waggle dance of honey bee (Apis mellifera L.) foragers communicates to nest mates the location of a profitable food source. We used solid-phase microextraction and gas chromatography coupled with mass spectrometry to show that waggle-dancing bees produce and release two alkanes, tricosane and pentacosane, and two alkenes, Z-(9)-tricosene and Z-(9)-pentacosene, onto their abdomens and into the air. Nondancing foragers returning from the same food source produce these substances in only minute quantities. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(116 citation statements)
references
References 23 publications
2
112
0
2
Order By: Relevance
“…In the social wasp, Vespa crabro, cuticular hydrocarbons including (Z)-9-tricosene are involved in the phenomenon of nestmate recognition (Ruther et al 2002). Thom et al (2007) reported that (Z )-9-tricosene along with three other hydrocarbons could be isolated from the scent of waggle-dancing foragers of the honeybee (Apis mellifera). These compounds are semiochemicals, inducing worker recruitment to the food source.…”
Section: Discussionmentioning
confidence: 99%
“…In the social wasp, Vespa crabro, cuticular hydrocarbons including (Z)-9-tricosene are involved in the phenomenon of nestmate recognition (Ruther et al 2002). Thom et al (2007) reported that (Z )-9-tricosene along with three other hydrocarbons could be isolated from the scent of waggle-dancing foragers of the honeybee (Apis mellifera). These compounds are semiochemicals, inducing worker recruitment to the food source.…”
Section: Discussionmentioning
confidence: 99%
“…First, it may be the case that dances performed by foragers in multiple-patriline colonies are more attractive to their nest mates, prompting a greater number of workers to orient and remain attentive to them. Our analysis of focal dancers did not indicate that dances performed in genetically diverse colonies conveyed more ''excitement'' or ''enthusiasm'' [at least, based on their tempo (Seeley et al, 2000)] than those performed in genetically uniform colonies, although they could have been more appealing to potential recruits based on parameters that we did not evaluate, such as the amplitude of the brief waggle movements, the release by dancers of pheromones that modulate nest mate behaviour (Thom et al, 2007), or a overall levels of activity on the dance floor. The fact that the focal dances were longer on average in multiple-patriline colonies may reflect an aspect of attractiveness that was not captured by our study.…”
Section: Discussionmentioning
confidence: 64%
“…SPME has been used previously to characterize volatile chemical profiles of honey bee queens (Gilley et al 2006;Huang et al 2009) and waggle-dancing honey bee workers (Thom et al 2007). We used 65-Îźm polydimethylsiloxane divinylbenzene SPME fibers (Supelco SPME fiber 57326U; Sigma-Aldrich, Bellefonte, PA, USA) because they capture the largest number of queen-produced volatiles compared to other fiber types (Gilley et al 2006;Huang et al 2009).…”
Section: Sampling Queen Volatile Profilesmentioning
confidence: 99%